The Effect of an Unrestrictive Diet Program (iDip) on Weight Management with Primary Focus on Protein and Fiber Intake and Calorie Reduction (P21-010-19). (13th June 2019) - Lee, Mindy; Applegate, Catherine; Emamaddin, Abrar; Erdman, John; Nakamura, Manabu
Abstract: Objectives: To develop a cost-effective program for safe weight loss and sustainable maintenance for overweight adults with associated comorbidities through dietary modifications. Methods: The approach of Individualized Diet Improvement Program (iDip) was to build knowledge of participants to enable personalized selection of food items for weight loss and maintenance with an emphasis on increasing protein and fiber intake and reducing calories. Fourteen adults with BMI ≥ 27 kg/m 2 and associated comorbidities were recruited. The study comprised of 22 diet improvement education sessions over 12 months with follow-up for 6 months. Daily self-weighing was required via Wi-Fi scale. Food Frequency Questionnaire (FFQ) data was collected at baseline and at 12 months. Feedback was provided for 24-hour records in the form of a protein-fiber (PF) plot, in which a target weight loss (protein: 7–11 g/100 kcal, fiber: 1.8–3.2 g/100 kcal) and maintenance (protein: 4–8 g/100 kcal, fiber: 1.4–2.8 g/100 kcal) box were plotted for easy target visualization. Results: Out of 14 participants, 12 (86%) completed all 22 diet improvement sessions and most of them weighed daily. All completers found the program beneficial. Mean weight loss at 6 months and 12 months was −6.1 kg ± 1.2 and −4.8 kg ± 1.4, respectively. Four participants did not lose weight but no significant weight gain from baseline was observed. Of these 4, 1 participant showed rebound weight gain (−14.5 kg at 6 months and + 0.7 kg at 12 months). Eight participants achieved weight loss with maintenance: mean weight loss at 6 months and at 12 months was −6.6 kg ± 1.1 and −7.8 kg ± 0.8, respectively. Although mean fiber intake showed no change from baseline (maintained at 1.3 g/100 kcal), overall PF plot dietary pattern moved toward the target weight loss box as the program continued. Mean protein intake at 6 months increased to 5.4 g/100 kcal ± 0.3 from 4.1 g/100 kcal ± 0.3 at baseline. Conclusions: The majority (67%) of participants successfully lost weight and maintained losses for 12 months without strict diet instructions, showing the feasibility of the informed decision-making approach. Further studies will be required to improve weight loss rates and develop an approach to no-responders. Funding Sources: USDA NIFA; NIBIB NIH (CA).